NGHIÊN CỨU TỐI ƯU HÓA QUÁ TRÌNH THỦY PHÂN CELLULOSE TÁCH TỪ RƠM RẠ THÀNH ĐƯỜNG TAN CỦA NÂM MỐC ASPERGILLUS TERRIUS ĐỂ SẢN XUẤT ETHANOL - NHIÊN LIỆU SINH HỌC - Toại, Trần Đình; Hải, Phạm Hồng; Kiên, Nguyễn Bá; Bích, Hoàng Thị; Sỹ, Đỗ Trung (Vietnam Journal of Science and Technology, 2012)
SUMMARY OPTIMIZATION OF THE CELLULOSE (FROM RICE STUBBLE/STRAW) HYDROLYSIS INTO GLUCOSE USING FUNGI ASPERGILLUS TERRIUS IN ETHANOL-BIOFUEL PRODUCTION The cellulose hydrolysis into glucose using Aspergillus terrius AF67 in ethanol-biofuel production was studied. By using the design of experiments with main factors (the concentrations of cellulose and enzyme) a regression equation was found. Based on this equation, the influent evaluation of two above factors on hydrolysis yield was implemented and with some supplementary experiments, the maximal yield was found:  ymax = 15.876 mg/ml. Keywords. Aspergillus terrius AF67